2017
DOI: 10.1007/s12155-017-9885-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects over the First 2½ Rotation Periods of a Fertilised Poplar Short Rotation Coppice

Abstract: A short rotation coppice (SRC) with poplar was established in a randomised fertilisation experiment on sandy loam soil in Potsdam (Northeast Germany). The main objective of this study was to assess if negative environmental effects as nitrogen leaching and greenhouse gas emissions are enhanced by mineral nitrogen (N) fertiliser applied to poplar at rates of 0, 50 and 75 kg N ha −1 year −1 and how these effects are influenced by tree age with increasing number of rotation periods and cycles of organic matter de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(76 reference statements)
2
4
0
Order By: Relevance
“…Estimates from the boreal forest showed that fine root biomass and N content of Populus stands respectively averaged 4800 kg/ha and 46.7 kg N/ha in the 0–20 cm soil layer 13 . This is well above the measured range for live fine root biomass (581.3–1642.6 kg/ha) and N content (4.91–13.23 kg N/ha), which corresponds to observations from other poplar plantations in the temperate zone 37,38 . Such high fine root biomass in boreal poplar stands vs. temperate old-field plantations likely reflects climate-related limitations in soil resource availability and in nutrient uptake rate by roots as latitude increases 46 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Estimates from the boreal forest showed that fine root biomass and N content of Populus stands respectively averaged 4800 kg/ha and 46.7 kg N/ha in the 0–20 cm soil layer 13 . This is well above the measured range for live fine root biomass (581.3–1642.6 kg/ha) and N content (4.91–13.23 kg N/ha), which corresponds to observations from other poplar plantations in the temperate zone 37,38 . Such high fine root biomass in boreal poplar stands vs. temperate old-field plantations likely reflects climate-related limitations in soil resource availability and in nutrient uptake rate by roots as latitude increases 46 .…”
Section: Discussionsupporting
confidence: 83%
“…Previous field studies with planted poplars have reported different conclusions related to the effect of abiotic and biotic factors on fine root biomass 3538,40,41 . Our regional-scale study, conducted in 14 year-old closed-canopy poplar plantations, provides evidence supporting the negative relationship hypothesis between soil fertility and fine root biomass 13 (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The impacts of SRC on water resources have been widely studied [3][4][5][6][7]. Soil-related investigations have mainly focused on the impacts of SRC on soil ecology [8][9][10][11][12][13], whereas changes on soil physical properties have been poorly studied. Evaluations of soil properties mainly occurred as part of an assessment of site characteristics affecting SRC size, quality and sustainability of yields [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Trees planted on agricultural land present an opportunity for producing biomass sustainably and at the same time improving farm income. Fast-growing tree species such as poplar, willow and black locust cultivated in short rotation coppices (SRC) or agroforestry systems (AFS) offer not only considerable potential for producing plant biomass, but can also at the same time withdraw carbon from the atmosphere and store it in their biomass [1][2][3][4][5][6]. To be successful in competition with wood products from the forestry sector, various obstacles need to be overcome when expanding the cultivation of fast-growing agricultural timber crops.…”
Section: Introductionmentioning
confidence: 99%